The Sounds of Disappearance - Guimond, David (Intermédialités / Intermediality, 2007)
Examining the microoperations of sound's physical properties moves us beyond the temporality that has functioned to dichotomize its appearances and disappearances as solely an experience of a “coming to” and a “fading away.” Characterized by a frenzy of heterogeneous activity at the physical level, sound has the ability to engender simultaneous registers of appearance and disappearance in which they are neither mutually exclusive nor can be clearly separated, inviting us to eschew the simplicity of their temporal dichotomization. Rather, the power of sound functions specifically because it forever intertwines its appearances and disappearances, simultaneously, in the creation of the sonic event with the listening subject.